Caratteristiche e funzioni delle componente paratestuali nelle edizioni rinascimentali italiane petrarchesche - Santoro, Marco (Cuadernos de Filología Italiana, 2005)
In virtue of the control carried out on several 15th/16th century Italian editions of the Canzoniere, an explanation is given to a series of editorial choices regarding the presentation of Petrarca’s work, gauged on the potential classification of reading and aimed at knowledgeably influencing the enjoyment of the same semantic message.